Xenophobia in South Africa: Alignment of policy-making with the aim of the Missio Dei (Mission of God) - Thinane, Jonas Sello (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2022)
Generally, the problem of xenophobia remains a complex and challenging topic for most countries of the world, for Africans and South Africans in particular. Constructed upon existing literature, this paper contributes to the discourse on anti-immigrant or xenophobic feelings in South Africa. This paper uses Missio Politica as a missiological framework combined with political theology to examine xenophobia. Although alluring further extensive research, it represents the neglected step in organising the vast body of missiological perspectives on the subject of xenophobia regarding the objective of the Missio Dei. It is entirely devoted to seeking answers to the question of xenophobia by appealing to the correct understanding of Missio Dei’s goal as demonstrated in the account of Noah's Ark in Genesis 6-9. Consequently, it concludes that to circumvent xenophobic incidents, African countries must first prioritise salvation for their local citizens, just as Noah did with his own family, before attempting to invite the entire continent into the tiny ark of salvation. Correspondingly, it concludes that South African policy-makers should familiarise themselves with important religious ideologies of their constituencies to shape public policies that are compatible with societal religious aspirations. Xenophobia has become an issue of great concern, particularly in South Africa. In the discipline of missiology, the current literature does not provide a clear methodology for solving xenophobia. This study represents the first missio politica analysis of the impact of xenophobia on the goal of Missio Dei.